TINJAUAN YURIDIS PENYIMPANGAN TERHADAP PIDANA MINIMUM DALAM TINDAK PIDANA NARKOTIKA (STUDI PUTUSAN NOMOR 33/Pid.Singkat/2020/PN.Mks) : JURIDIC REVIEW OF DIFFERENCES AGAINST MINIMUM CRIMINAL ACTIONS IN NARCOTICS (STUDY OF DECISION NUMBER 33/Pid. Brief/2020/PN.Mks) - Sinta, Atifa Batara; Oner, Basri; Zubaidah, Siti (Clavia, 2021)
This study aims to determine the judge's consideration in imposing sanctions under the minimumsentence in the verdict case number 33 / Pid. Brief / 2020 / PN.Mks and to find out the sanctionsfor judges who impose sentences under the minimum criminal sanction. The research methodused is normative legal research. Types and sources of data consist of primary data in the formof statutory regulations, Supreme Court Circular Letters and Court Decisions as well assecondary legal materials consisting of books, articles and journals related to this research. Alllegal materials were analyzed qualitatively and presented descriptively analysis.The results show that the judge's consideration in imposing criminal sanctions under theminimum sentence is based on the Supreme Court Circular (SEMA) Number 3 of 2015 whichbasically allows judges to deviate from the minimum crimes in Article 111 and Article 112 of theNarcotics Law. Then there are no sanctions for judges who impose a sentence under theminimum sentence, but every judge's decision that deviates from the minimum sentence must be followed by sufficient consideration, both juridical and sociological considerations.